Peran Komisi Pemberantas Korupsi (KPK) Dalam Menangani Kasus Korupsi di Indonesia - Ayu Winda Amelia; Keilla Anabila; Nur Amalia Zahra (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The Corruption Eradication Commission (KPK) plays a crucial role in combating corruption in Indonesia. This institution was established to address various corruption cases involving public officials, with the aim of increasing transparency, accountability, and justice in government administration. However, KPK faces numerous challenges in carrying out its duties, such as revisions to laws that limit its authority and obstacles in coordination with other law enforcement agencies. The factors causing corruption in Indonesia are complex, including weak oversight, a permissive culture towards corruption, and lack of transparency in state budget management. KPK not only focuses on taking action against corruption perpetrators but also strives to recover state losses through asset confiscation mechanisms. Despite this, KPK's effectiveness in combating corruption is often hindered by both internal and external challenges. Therefore, it is important to continuously strengthen coordination among law enforcement agencies and encourage legal reforms to enhance this institution. With stronger commitment from all parties, corruption eradication in Indonesia can be more effective, leading to a clean government free from corruption practices.